2020
DOI: 10.5489/cuaj.6676
|View full text |Cite
|
Sign up to set email alerts
|

Does adding local salvage ablation therapy provide survival advantage for patients with locally recurrent prostate cancer following radiotherapy?

Abstract: Introduction: Some men who experience prostate cancer recurrence post-radiotherapy may be candidates for local salvage therapy, avoiding and delaying systemic treatments. Our aim was to assess the impact of clinical outcomes of adding salvage local treatment in prostate cancer patients who have failed radiation therapy. Methods: Following radiation biochemical failure, salvage transperineal cryotherapy (sCT, n=186), transrectal high intensity focused ultrasound ablation (sHIFU, n=113) or no salvage treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Among the 26 studies [23][24][25][26][27][28][29][30][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] included (Table 3…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 26 studies [23][24][25][26][27][28][29][30][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] included (Table 3…”
Section: Resultsmentioning
confidence: 99%
“…In 11 studies, 2,101 patients (age range 56-79 years) underwent salvage cryotherapy with the PSA ranging from 0.01 to 31.60 ng/mL. Nine studies [30,[37][38][39]41,45,46,49,54] reported histological staging, and one study [54] reported 7 as the median Gleason score. The remaining studies [51,53] encompassed 536 patients with PSA < 7 ng/mL, 478 patients with PSA = 7 ng/mL and 378 patients with PSA > 7 ng/mL.…”
Section: Salvage Cryotherapy Studiesmentioning
confidence: 99%
See 3 more Smart Citations